Knowledge, attitudes, and practices for the use of seasonal influenza vaccination, healthcare workers, Costa Rica - Zachary Madewell; Rafael Chacón-Fuentes; Xiomara Badilla-Vargas; Catalina Ramirez; Maria-Renee Ortiz; Juan-Pablo Alvis-Estrada; Jorge Jara (Journal of Infection in Developing Countries)
Introduction: Annual seasonal influenza vaccination in healthcare workers prevents nosocomial transmission to patients, coworkers, and visitors, and reduces absenteeism. This study aimed to describe knowledge, attitudes, and practices (KAP) of seasonal influenza vaccine among public healthcare workers attending patients in Costa Rica.